Using real-time location data to calculate propulsive power output and analyze performance in cross-country skiing - Swaren, M.; Stöggl, T.; Supej, M.; Eriksson, A. (Science and Skiing VII, 2018)
Cross-country sprint skiing (XCSS) is an event with race times of approximately three minutes and an average track length of 1,350 m (Stöggl, Lindinger, & Müller, 2006). The XCSS discipline consists of two parts: a time trial (qualification heat) where each athlete skis around the course individually, and the finals which consist of three successive knockout heats with approximately 20 minutes of rest between them. XCSS is a physically demanding sport and, as the skier`s resources of energy are limited, the produced power output should be distributed in a rational way. Good tactics and positioning skills are therefore essential abilities for a XC sprint skier. The large element of tactics in XCSS increases the importance of accurate, continuous, and objective performance analyses. Previous studies on XCSS have primarily involved satellite navigational systems (Andersson et al., 2010; Larsson & Henriksson-Larsen, 2005). For example, Andersson et al. (2010) employed a realtime kinematic global navigation satellite system (RTK GNSS) in combination with a video camera on a snowmobile to achieve detailed analysis of the skier`s velocity, technique, and tactics. However, the RTK GNSS system is bulky, and the skier must carry a backpack containing the rover (~1.6 kg). It is also expensive and the additional cost per athlete is high when collecting data from multiple athletes simultaneously which makes this system not suitable to be used during competitions.